2013
DOI: 10.1212/wnl.0b013e318299ccd9
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-ophthalmologic evaluation, quality of life, and functional disability in patients with MS

Abstract: Patients with progressive axonal loss as seen in RNFL results had a lower QOL and more functional disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 30 publications
3
41
0
7
Order By: Relevance
“…We also confirmed the results of previous studies that indicate a tendency of RNFL atrophy to be greater in ON-affected eyes than in unaffected eyes [20,21,22]. Previous studies reported that RNFL thickness was correlated with functional and structural measures of MS such as visual acuity, visual field, low-contrast letter acuity, contrast sensitivity, color vision, visual evoked potentials, brain atrophy assessed by magnetic resonance imaging and even quality of life [16,23,24,25,26]. In our study no correlation was found between RNFL and choroidal thickness measurements in both MS ON and MS non-ON eyes.…”
Section: Discussionmentioning
confidence: 99%
“…We also confirmed the results of previous studies that indicate a tendency of RNFL atrophy to be greater in ON-affected eyes than in unaffected eyes [20,21,22]. Previous studies reported that RNFL thickness was correlated with functional and structural measures of MS such as visual acuity, visual field, low-contrast letter acuity, contrast sensitivity, color vision, visual evoked potentials, brain atrophy assessed by magnetic resonance imaging and even quality of life [16,23,24,25,26]. In our study no correlation was found between RNFL and choroidal thickness measurements in both MS ON and MS non-ON eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have analysed the ability of OCT to detect RNFL thickness abnormalities and changes in the macula of patients with neurodegenerative diseases. 10,11 Retrograde loss of nerve fibres in the retina and optic nerve may be an early biomarker of neurodegeneration in AD, even before hippocampal damage, which leads to memory impairment. 12 Recent studies have revealed the value of RNFL and macular measurements provided by OCT for detecting neurodegenerative disease progression and facilitating the diagnosis of diseases such as multiple sclerosis 10,13,14 and Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Retrograde loss of nerve fibres in the retina and optic nerve may be an early biomarker of neurodegeneration in AD, even before hippocampal damage, which leads to memory impairment. 12 Recent studies have revealed the value of RNFL and macular measurements provided by OCT for detecting neurodegenerative disease progression and facilitating the diagnosis of diseases such as multiple sclerosis 10,13,14 and Parkinson's disease. 15,16 Therefore, in the present study we evaluated the reliability of retinal and RNFL applications of the two most commonly available FD-OCT devices, the Cirrus (Carl Zeiss Meditec Inc., Dublin, CA, USA) and Spectralis (Heidelberg Engineering, Inc., Heidelberg, Germany), for detecting retinal thinning and RNFL atrophy in patients with AD.…”
Section: Introductionmentioning
confidence: 99%
“…18 Correlations between RNFL morphology and neurophysiology are also reported. 19,20 Consideration of patient quality of life (QOL) is intrinsic to the practice of medicine, particularly when evaluating therapeutic approaches to chronic disease. 21 In PD, fatigue and fatigability levels are higher than in healthy individuals, and are negatively associated with QOL scores.…”
mentioning
confidence: 99%